The Importance of Keratinized Mucosa Around Dental Implants - Li, Xinda; Horvath, Attila (Archive of Orofacial Data Science, 2025)
AIM: The objective of this review is to determine the efficiency of different augmentation materials in increasing the ideal width and thickness of peri-implant keratinized mucosa (PIKM) and thereby achieving stable peri-implant health. To this end, various clinical parameters will be analyzed for the different techniques employed and the initially achieved PIKM width and thickness. METHODS: An electronic search of the literature from 2009 to 2019 was conducted in PubMed for studies addressing peri-implant keratinized mucosa and peri-implant health, in combination with peri-implant soft tissue augmentation. RESULTS: The initial search identified 311 studies, of which 28 passed the first review phase, resulting in 19 studies selected based on established criteria. Insufficient peri-implant keratinized mucosa width (< 2 mm) correlates with inflammation. The combination of autogenous grafts (free gingival grafts) and an apically positioned flap is the gold standard for gaining PIKM width, while xenogeneic materials may offer a short-term alternative. For increasing PIKM thickness, Alloderm, Mucoderm, or autogenous grafts used in augmentation procedures significantly reduced marginal bone loss. CONCLUSION: PIKM width under 2 mm should be avoided due to its association with increased marginal bone loss and inflammation. Autograft augmentation combined with an apically positioned flap is the gold standard, while allogenic and xenogenic materials also yield successful outcomes.